Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond - Kumer , Peter; Davidović, Danijel (2026)
Contemporary societies are shaped by increasingly rapid and interconnected global changes, including technological acceleration, environmental pressures, and social transformations, which continuously reshape everyday life and spatial realities. As a consequence of these dynamics, quality of life has gained increasing relevance in contemporary research. The scientific monograph addresses quality of life in a holistic manner, through an interplay of spatial, social, and environmental perspectives, based on an empirical framework that draws on diverse case studies from Maribor and the wider European context. A particular strength of the monograph lies in its international and collaborative character, as it brings together contributions from students and researchers from different disciplines and countries, reflecting contemporary research approaches and enriching the understanding of quality of life as a multidimensional theme. The chapters reflect methodological diversity, the use of a combination of qualitative and quantitative approaches, fieldwork, spatial analyses, and cartographic representations.. As a whole, the monograph represents an important contribution to the study of medium-sized cities, regional geography, and quality of life, while also offering significant pedagogical and applied value for further research and policy-making.
Keywords: quality of life; well-being; spatial development; spatial inequality; sustainable urban development; public space